The Role of Language Acquisition Theory in Arabic Online Learning (Skinner’s Behaviorism Perspective) - Moh. Faza Rosyada; Muhammad Sya'dullah Fauzi; Adik Laila Fitri Nawangsari (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This article aimed to find out what the role of behaviorist language acquisition theory in learning Arabic online from the perspective of BF. Skinner. This research was a literature review that explores information about the role of language acquisition theory in learning Arabic, especially the idea of behaviorism according to BF Skinner's view. This research showed that the theory of BF Skinner's language acquisition plays a role in learning Arabic because it can help teachers determine what kind of technology media and methods will be used by teachers in learning Arabic. In selecting technology media and learning methods, Arabic teachers should use Synchronous Learning-based media and techniques as much as possible. Synchronous Learning is online learning with direct communication, such as using the Zoom cloud meeting application. Because the purpose of learning Arabic can be achieved if there is habituation in the four language skills, the teachers can also determine the reward or reinforcement for Arabic language learners according to the learners' psychological condition so that learners will be encouraged to improve their language skills even in online learning conditions continuously.